Treating Pediatric Asthma According Guidelines - Tesse, Riccardina; Borrelli, Giorgia; Mongelli, Giuseppina; Mastrorilli, Violetta; Cardinale, Fabio (Frontiers in Pediatrics, 2018)
Asthma is a common chronic inflammatory disorder of the lower respiratory airways in childhood. The management of asthma exacerbations and the disease control are major concerns for clinical practice. The Global Strategy for Asthma Management and Prevention, published by GINA, updated in 2017, the British Thoracic Society/Scottish Intercollegiate Guideline Network, revised in 2016, the National Institute for Health and Care Excellence asthma guideline consultation, available in 2017, are widely accepted documents, frequently implemented, with conflicting advices and different conclusion on asthma definition and treatment. An International Consensus on Pediatric Asthma was carried out in 2012 by a Committee with expertise in the field, to critically review differences on current guidelines. In addition, the specific issue of treating severe and difficult asthma has been recently highlighted throughout the International European Respiratory Society/American Thoracic Society guidelines on severe asthma. The aim of this paper is to describe conventional treatments and some new therapeutic approaches to pediatric asthma according to guidelines, highlighting differences on proposed clinical recommendations for asthma management. Age specific therapy are proposed in steps, according to clinical severity and the level of disease control. If control is not achieved within 3 months, stepping-up should be considered; otherwise, if control is achieved after 3 months, stepping down may be considered. The most used drug classes of asthma medications are beta-2 adrenergic agonists, corticosteroids, and leukotriene modifiers. Intramuscolar triamcinolone has been used for severe asthma treatment. Chromones and xanthines have been extensively used in the past, but they have shown limits related to their efficacy and safety profile. Omalizumab, a monoclonal antibody against IgE, is an immunomodulatory biological agent, used as new drug in patients with confirmed IgE-mediated allergic asthma, only for patient’s specific range of total IgE level. There are low evidences in the efficacy of metotrexate, as well as macrolide antibiotics in children with asthma. Antifungal agents are also not recommended in asthmatic patients. Non pharmacological measures that may improve patient’s quality of life should also be attempted We conclude that treatment decisions on childhood asthma management should be critically made, pondering the differences suggested by agreed international consensus documents.